Evaluating the causative factors that lead to rejection of hearing aids among young adults having moderate to severe degree sensorineural hearing loss (Journal of Fatima Jinnah Medical University, 2021)
Background: Hearing loss in young adulthood causes real stigma and a state of denial. The crucial clinical management to sustain the hearing loss is hearing aid fitting, but most adult people reject it or do not use it. Many factors, including social, personal, and device problems, lessen the usage of hearing aid. The objective of this study was to evaluate the causative factors which can lead to the rejection of hearing aids. Patients and methods: This was a cross-sectional survey carried out in 9 cities of Punjab, Pakistan, using a convenient sampling technique during summer 2018. A total of 171 participants were included who were young adults ranging from 19-40 years. A questionnaire with 11 factors and a further 35 sub-reasons was given to the participants. Questions were close-ended in yes or no. Data were analyzed through frequency and percentages tabulation with SPSS software.Results: Results showed that hearing aid value/speech clarity was the most problematic reason for patients to reject hearing aid. The given factor had four sub-reasons ('noisy situation,' 'poor benefit,' 'poor sound quality, and 'not suitable for the type of hearing loss). A total number n=154 (90.05%) marked yes for facing poor sound quality followed by poor benefit n=141 (82.45%), not suitable for the type of hearing loss n=121 (70.76%) and noisy situation n=118 (69.00%), thus making hearing aid value the leading cause of rejection. The second leading cause was financial factors followed by situational factors, appearance, fit and comfort, device factors, psychosocial factors, ear infections, care and maintenance, attitude, and family pressure to use a hearing aid. Conclusion: Most prevalent cause of not taking up a hearing aid is the hearing aid value followed by financial factors, situational factors, appearance, fit, and comfort.
Keywords: Young adulthood; Hearing aids; Hearing impairment; Rejection; Factors